Penerapan Model Numbered Heads Together Berbantuan Media Binomera (Bingo Numerasi Operasi Matematika) untuk Meningkatkan Hasil Belajar Matematika Siswa Sekolah Dasar - Jannah, Fullu; Fardani, Much Arsyad; Hamim, Nurul (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to improve mathematics learning outcomes on multiplication and division material through the implementation of the Numbered Heads Together learning model assisted by Binomera (Bingo Numerasi Operasi Matematika) for second-grade students at SD 2 Medini Kudus. The research employed the Kemmis & McTaggart Classroom Action Research model and was conducted in two cycles during the even semester of the 2024/2025 academic year. Each cycle consisted of planning, implementation, observation, and reflection stages. The subjects of this study were 27 second-grade students. Data were collected through learning outcome tests and observations. The results showed an improvement in student learning outcomes, with mastery increasing from only 19% in the pre-cycle stage with an average score of 41.48, to 44% in the first cycle with an average of 68.14, and finally reaching 81% in the second cycle with an average of 81.29. These findings indicate that the implementation of the Numbered Heads Together learning model assisted by Binomera media can enhance student learning outcomes. The findings provide a strong foundation for further development and broader application of the method in the context of primary education